Particle Size Distribution and Rheolog ical Characteristic of Trimethylolethane Treated by Cationic Surfactant - Yuli Setyo Indartono; Hiromoto Usui; Hiroshi Suzuki; Satoshi Tanaka; Kousuke Nakayama; Yoshiyuki Komoda; Tetsu Itotagawa (Mesin, 2007)
Trimethylolethane (TME) trihydrate particle suspended in water is a proper substance for latent heat transportation in cooling systems, since it has high heat transfer and thermal capacity. Additives, oleyl bishydroxyethyl methyl ammonium chloride as surfactant and sodium salicylate as counter-ion, were added into TME slurry to reduce its friction factor. Aditives influence on particle size distribution and rheological characteristic of TME are investigated in this study. It is found that the additives do not influence particle size at crystallization point, but they clearly inhibit further particle growth. By increasing molar ratio of counter-ion to surfactant, the particles do not grow at all. Increasing TME concentration reduces the apparent viscosity of TME with surfactant and increases critical shear rate for Shear Induced Structure (SIS) occurrence. By connecting this SIS phenomenon with previous data, it is found that there is a relation between the SIS and drag reduction for this drag-reducing TME suspension system.